OOCYTE DEVELOPMENT AND ANNUAL CYCLE OF OVARIAN COMPOSITIONS IN THE REDBELLY YELLOWTAIL FUSILIER Caesio Cuning (BLOCH) FROM THE KARIMUNJAWA WATERS - Susilo, E. S.; Harnadi, S. L.; Takemura, A. (Marine Research in Indonesia, 2008)
Histological examination of gonad of female redbelly yellowtail fusilier Caesio cuning was carried out in order to describe the oocyte development and annual changes of ovarian composition. The oocyte development was devided into seven stages: peri-nucleolus (PN), oil-droplet (OD), primary yolk (PY), secondary yolk (SY), tertiary yolk (TY), migratory (M) and maturation (Mt) stages. The histological examination of ovarian composition showed that the fish had three peak spawning seasons: in June-July, October-November and February-March. Various kind of developing oocytes found in the same ovaries suggested multiple spawner and asynchronous type of ovarian dynamic.